The Effect of Interpersonal Communication and Work Discipline on Employee Performance at PDAM Tirta Randik, Babat Toman Branch - M. Nurul Huda; Roswaty Roswaty; Muhammad Kurniawan DP (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This study aims to analyze the effect of interpersonal communication and work discipline on employee performance at PDAM Tirta Randik, Babat Toman Branch. The sample in this study was 49 respondents who were collected through a questionnaire. This study utilized multiple linear regression method to analyze the data. This research prove that partially, interpersonal communication and work discipline have a significant effect on employee performance. Simultaneously, interpersonal communication and work discipline have a significant and positive effect on employee performance. This research is expected to be useful for PDAM Tirta Randik, Babat Toman Branch to improve employee performance through interpersonal communication and work discipline factors.